Medical ethics in Dr. Narciso LLamos Sierra: stronghold of the higher medical education in Santiago de Cuba - Zaida Espino La O; Natacha Lidia Álvarez Pérez (Centro Provincial de Información de Ciencias Médicas, 2016)
The qualities of Dr. Narciso Llamos Sierra are exalted, Demerit, Instructor and Consultant Professor of Medicine; recognized as stronghold of the medical education in Santiago de Cuba for his dedication, abnegation, modesty, lack of interest, humanism, educational and clinical diagnosis methods. His contributions were useful to stimulate learning and ethical - humanist values formation in his students.